Utilizing study and site performance metrics to improve efficiency of clinical trials: An initiative of the Alzheimer's Clinical Trials Consortium (ACTC). (31st December 2021) - Walter, Sarah; Craft, Suzanne; Geldmacher, David S.; Menard, William; Sano, Mary; Obisesan, Thomas O; Combs, Martha; Gessert, Devon; Shaffer‐Bacareza, Elizabeth; Miller, Garrett; Donohue, Michael C; Rafii, Michael S; et al.
Abstract: Background: The Alzheimer's Clinical Trials Consortium (ACTC) aims to provide an optimal infrastructure, utilizing centralized resources and shared expertise, to accelerate the development of effective interventions for Alzheimer's disease and related disorders (ADRD). Metrics help clinical research sites understand where they stand relative to other sites and share best practices. For ACTC and study leaders, metrics aid in tracking the progress towards established goals, assessing performance of the sites and of the coordinating center in supporting site efforts, and may identify areas where additional development is needed. Method: This initiative is led by an ACTC committee, comprised of member site PIs, research staff, and ACTC's coordinating center. Proposed metrics were approved by the ACTC Steering Committee, and include those typically used to assess performance of a clinical trial (i.e., screening and randomization totals) as well as information not typically quantified (e.g. PI oversight and responsiveness). Reports are generated by extracting data from the ACTC data system, which ensures accuracy and minimizes site burden. A key element of this initiative is feedback from sites, obtained ad hoc and semiannually. Surveys were also used to understand the impact of COVID‐19 pandemic and other barriers to study startup. Interactive reports are distributed quarterly, facilitating both high level and detailed review. Site‐specific anonymized reports allow sites to see how they are performing relative to other sites. Result: 5 surveys were distributed with response rates between 50% and 82%. Quarterly reports, including summaries of site activation and screening performance, were distributed to 75 sites. Results obtained will be in our presentation. Conclusion: We established procedures to collect, report and disseminate metrics, providing the foundation for a strong connection between sites and study teams. Our next steps are to develop additional summaries, maximize survey responses, improve the efficiency of report dissemination, as well as to explore the utility of metrics in measuring efficiency of trial conduct. This initiative will inform the development and implementation of additional ACTC trials, as well as tracking ACTC progress in building a consortium responsive to a changing landscape of clinical trials.